Organizational Happiness: Job Crafting Dan Work Engagement - Harahap, Abu Hanipah; Handayani, Ririn; Bastian, Adolf (Jurnal Ekonomika Dan Bisnis (JEBS), 2025)
The research was conducted at the Representative BPK of Riau Province, with the aim of examining the role of organizational happiness in mediating the influence of job crafting on work engagement. The population of this study was 155 people. Based on this population size, in accordance with the Krejcie and Morgan (1970) table, the sample size for this study was 108 people. The sampling method used in this research is Systematic Random Sampling. All respondents will be used to obtain primary data related to the variables, which will be collected through a questionnaire with a 1-5 point Likert scale. All data obtained will be analyzed using Structural Equation Modeling (SEM) with the Smart PLS 3.0 analysis tool. This research finds that job crafting has a significant positive effect on work engagement results; and mediating organizational happiness has a significant positive effect on job crafting on work engagement.